PERBANDINGAN ALGORITMA C4.5, KNN, DAN NAIVE BAYES UNTUK PENENTUAN MODEL KLASIFIKASI PENANGGUNG JAWAB BSI ENTREPRENEUR CENTER (Jurnal Pilar Nusa Mandiri, 2018)
BSI Entrepreneur Center is one of the organizations engaged in entrepreneurship within the Bina Sarana Informatika University with the aim of forming students who want to become entrepreneurs. Currently BSI Entrepreneur Center has had responsibility in each campus of Bina Sarana Informatika University. But the existing human resources have not been able to fulfill the needs as the person in charge of BSI Entrepreneur Center to be placed on each campus of Bina Sarana Informatika University. Therefore, a system is needed to find appropriate human resources to be in charge of the BSI Entrepreneur Center on each campus of the Bina Sarana Informatika University. This study uses primary data as many as 300 records consisting of 12 attributes with the algorithm method C.45, KNN and Naive Bayes to classify employees according to the existing criteria. And the results of this study are suggestions from employees who are eligible to be in charge of BSI Entrepreneurs Center on each campus of the Information Technology Development University with the Naive Bayes method which has a high accuracy of 80%.
Keywords: BSI enterpreneur Center; Naive bayes method; Employee